Association between background exposure to organochlorine pesticides and the risk of cognitive impairment: A prospective study that accounts for weight change. (April 2016) - Lee, Duk-Hee; Lind, P. Monica; Jacobs, David R.; Salihovic, Samira; van Bavel, Bert; Lind, Lars
Abstract: Background: Background exposure to organochlorine (OC) pesticides was recently linked to cognitive impairment and dementia in cross-sectional and case–control studies. This prospective study was performed to evaluate if OC pesticides at baseline are associated with the future risk of cognitive impairment in elderly, with particular focus on weight change. Methods: Plasma concentrations of 3 OC pesticides (p, p′-DDE, trans-nonachlor, and hexachlorobenzene) were measured among 989 men and women aged 70 years in the Prospective Investigation of the Vasculature in Uppsala Seniors (PIVUS). Cognitive impairment was validated by reviewing medical records. During the ten year follow-up, cognitive impairment was developed in 75 subjects. When weight change from age 70 to 75 was considered in analyses, elderly with incident cases before age 75 were excluded to keep the prospective perspective, leaving 795 study subjects and 44 incident cases. Results: The summary measure of 3 OC pesticides predicted the development of cognitive impairment after adjusting for covariates, including weight change. Compared to subjects with OC pesticides < 25th percentile, adjusted hazard ratios (HRs) in those with 25th–<75th and ≥ 75th percentiles were 3.5 (95% confidence interval: 1.5–8.5) and 3.2 (1.1–7.6), respectively (Ptrend  = 0.04). Among 506 subjects who maintained or gained body weight, adjusted HRs were 6.9 and 11.6 (1.4–92.6) among the elderly in the 25th–<75th and ≥ 75th percentiles compared to < 25th percentile (Ptrend  < 0.01). Conclusions: This prospective study demonstrates that background exposure to OC pesticides are linked to the risk of developing cognitive impairment in elderly. The role of the chronic exposure to low dose OC pesticides in the development of dementia should be further evaluated in other populations. Highlights: Organochlorine pesticides predicted the development of cognitive impairment. Elders with high vs. low concentrations of organochlorine pesticides had about 3 times higher risks. These associations were observed even after considering weight change.